Effectiveness of Hatha Yoga Versus Conventional Therapeutic Exercises for Chronic Non-Specific Low-Back Pain: A Comparative Study on Yoga and Conventional Therapeutic Exercises for Chronic Low-Back Pain (Journal of Advances and Scholarly Researches in Allied Education, 2022)
We set out to compare the pain-relieving and functional-regaining effects of Hatha yoga therapyfor people with CNLBP to those of more traditional therapeutic activities (CTEs). Supervised interventionwas provided for a total of 6 weeks, followed by 6 weeks of follow-up. The Centre for Integrative Medicineand the Department of Physical Medicine and Rehabilitation at a large medical centre performed theresearch. Patients aged 18–55 had a 12-week history of CNLBP and a pain level of 4 on the numeric painrating scale. (0–10). People with CNLBP who are new to either Hatha yoga or CTE will benefit from sixweekly, 35-minute yoga sessions (yoga group) and six every week, 35-minute CTE sessions (CTE group).On non-class days, participants were instructed to practise at home. Use of pain medications weekly andsubjective improvement in back-related dysfunction following the intervention were secondaryoutcomes. Outcomes were recorded at three time points at baseline, after six weeks, and after twelveweeks. Seventy people were split into two groups at random yoga (n = 35) and cognitive trainingexercises (CTE). The newest observation was included in the analysis under the intention to treatpremise. Participants in both the yoga and CTE groups reported statistically significant improvements intheir back pain and back-related dysfunction at the 6- and 12-week follow-ups, relative to their baselineevaluations. Similar gains were seen in both groups' adherence to prescribed medications and theirsense of progress towards recovery. Patients with CNLBP reported the same level of relief from yoga asthey did with CTEs.